Bedside Ultrasound Measurement of Rectus Femoris: A Tutorial for the Nutrition Support Clinician - Carlos Alfredo Galindo Martín; Enrique Monares Zepeda; Octavio Augusto Lescas Méndez (Journal of Nutrition and Metabolism)
Intensive care unit acquired weakness is a long-term consequence after critical illness; it has been related to muscle atrophy and can be considered as one of the main nutritional support challenges at the intensive care unit. Measuring muscle mass by image techniques has become a new area of research for the nutritional support field, extending our knowledge about muscle wasting and the impact of nutritional approaches in the critical care setting, although currently there is no universally accepted technique to perform muscle measurements by ultrasound. Because of this, we present this tutorial for nutrition support clinicians, in order to understand and perform muscle measurements by this reliable, accessible, low-cost, and easy-to-use technique. Reviewing issues such as quadriceps muscle anatomy, correct technique (do’s and don’ts), identification of structures, and measurement of the rectus femoris and vastus intermedius muscles helps to acquire the basic concepts of this technique and encouraging more research in this field.